Systemic artery aneurysms – A marker of high-risk Kawasaki disease - Lamk Kadiyani; Shivaprasad P Mohankumar; Praveen Arumugam; Saurabh Kumar Gupta; Narendra Kumar Bagri; Niraj Pandey; Sanjeev Kumar (Annals of Pediatric Cardiology)
Kawasaki disease, traditionally classified as medium vessel vasculitis, is known for the preferential involvement of coronary arteries. Infrequently, large systemic arteries might be involved and may affect the prognosis. Here, we present an infant with Kawasaki disease who had extensive involvement of large vessels such as the abdominal aorta and medium vessels of the extremities, along with giant coronary artery aneurysms.